Implementasi Program Unggulan Tahfidz Al-Qur’an di Pondok Pesantren Tarbiyatun Nasyi’in Al-Minhaaj Desa Wates Kediri - Fina Fathatul Khoirot; Zuyyina Candra Kirana (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
The problems that have been found are that there are students who are less able to share their time to memorize the Qur'an, lack enthusiasm in memorizing, there are less representative facilities, lack of firmness in a regulation so that it affects the target of memorization which should be the target of memorizing in 2.5 years have been able to complete 30 juz and there is even a target in about 6 months to be able to complete 30 juz. This study uses a type of qualitative descriptive research with data collection techniques of interviews, observation, documentation. The flagship program of tahfidz al-Qur'an at the Tarbiyatun Nasyi'in Al-Minhaaj Islamic boarding school has four strategies,namely additional deposits, muroja'ah, tests/exams and acceleration. And there are supporting and inhibiting factors. In carrying out the tahfidz al-Qur'an flagship program, it is carried out through the involvement of several related parties such as foundations, caregivers, coaches, santri guardians, coordinators of each division in the tahfidz al-Qur'an flagship program with various parties rather than doing it independently in solving complex problems and finding appropriate solutions. So that the problem is quickly resolved properly.